High Antimicrobial Susceptibility of Cloacal Enterococci and Escherichia coli from Free-Living Dalmatian and Great White Pelicans with Detection of Cefotaximase CTX-M-15 Producing Escherichia coli ST69 - Teresa Cardona-Cabrera; Sandra Martínez-Álvarez; Carmen González-Azcona; Carlos Javier Gijón-García; Olga Alexandrou; Giorgos Catsadorakis; Panagiotis Azmanis; Carmen Torres; Ursula Höfle (Antibiotics)
Background/Objectives: In 2022, an outbreak of H5N1 highly pathogenic avian influenza (HPAI) killed 60% of the largest breeding colony of Dalmatian pelicans (DPs) in the world at Mikri Prespa Lake (Greece), prompting a multidisciplinary study on HPAI and other pathogens. This study determines the antimicrobial resistance rates of cloacal enterococci and Escherichia coli in DPs. Methods: Fifty-two blood and cloacal swab samples were collected from 31 nestlings (20 DP/11 great white pelicans) hatched after the H5N1 outbreak at the Prespa colony and 21 subadult/adult DPs captured at a spring migration stopover. The swabs were inoculated in non-selective and chromogenic-selective media. Identification was performed using MALDI-TOF, and antimicrobial susceptibility was tested. The genetic content was characterized using PCR and sequencing, and the clonality of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli isolates was characterized using Multilocus Sequence Typing. Results: Twenty-eight non-repetitive E. coli and 45 enterococci isolates were recovered in non-selective media; most of them were susceptible to all antibiotics tested (85.7% E. coli/91.1% enterococci). Three of the fifty-two samples (6%, all adults) contained ESBL-E. coli isolates (detected in chromogenic ESBL plates), all carrying the blaCTX-M-15 gene and belonging to the lineage ST69. Conclusions: Despite the susceptibility of most fecal E. coli and enterococci isolates to all antibiotics tested, the finding that E. coli of lineage ST69 carry blaCTX-M-15 is of concern. This high-risk clone needs further investigation to elucidate its primary sources and address the growing threat of antimicrobial resistance from an integrated “One Health” perspective. Furthermore, it is imperative to study the potential impacts of ESBL-E. coli on the endangered DP further.